2013
DOI: 10.33577/2312-4458.8.2013.50-56
|View full text |Cite
|
Sign up to set email alerts
|

Interaction process model of between reconnaissance-signaling platform and object of detection based on characteristics of operative-tactical situation

Abstract: В статті представлено модель процесу взаємодії розвідувально-сигналізаційного комплексу з об'єктом виявлення, яку розроблено з використанням технології аналітичного моделювання дискретно-неперервних стохастичних систем. При розробці моделі враховано особливості місцевості (тип ґрунту, рельєф), пори року, розташування об'єкту, що охороняється, та наявність радіозавад.Ключові слова: розвідувально-сигналізаційний комплекс, автономна система виявлення і класифікації об'єктів, система передавання радіоповідомлень, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Suggested mathematical model of GSC reaction on MO appearance with pairwise SS S placement in far and close control zones, and also model of GSC reaction given in [1,2] have the necessary level of adequacy and allow receiving reliable results concerning effectiveness of its work.…”
Section: Results Of Comparative Analysis Of Gsc Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations
“…Suggested mathematical model of GSC reaction on MO appearance with pairwise SS S placement in far and close control zones, and also model of GSC reaction given in [1,2] have the necessary level of adequacy and allow receiving reliable results concerning effectiveness of its work.…”
Section: Results Of Comparative Analysis Of Gsc Effectivenessmentioning
confidence: 99%
“…In order to research the effectiveness of GSC in the articles [1,2] it is suggested to use the mathematical model of the reaction of GSC on the movement of the MO in the distant and close zones of control. Two SSs are installed serially along the route.…”
Section: Analysis Of Researches and Publicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…2. Публікації з обґрунтуваннями доцільності (з рекомендаціями) поєднання різних типів систем виявлення БпЛА в один радіоелектронний комплекс [10,15,16,17].…”
Section: аналіз останніх досліджень та публікаційunclassified